2022
DOI: 10.1111/medu.14968
|View full text |Cite
|
Sign up to set email alerts
|

Using fairness to reconcile tensions between coaching and assessment

Abstract: Coaching is dedicated to supporting learners' personal and professional development to assist them reach their potential. 1 In contrast, traditionally, assessment has been focused on achievement or selecting out the 'bad apples'. From this perspective,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Comparing the experiences of our undergraduate mentors and mentees to those of participants in other research we noticed underlying similarities. The fact that combining developmental support and assessment is possible under certain conditions was also concluded elsewhere [11,26,41]. Valentine and Schuwirth [41], for example, concluded that assessment by a coach needs to be perceived as 'fair' (credible, transparent, fit for purpose, and accountable), for a learner to accept it and learn from it.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Comparing the experiences of our undergraduate mentors and mentees to those of participants in other research we noticed underlying similarities. The fact that combining developmental support and assessment is possible under certain conditions was also concluded elsewhere [11,26,41]. Valentine and Schuwirth [41], for example, concluded that assessment by a coach needs to be perceived as 'fair' (credible, transparent, fit for purpose, and accountable), for a learner to accept it and learn from it.…”
Section: Discussionmentioning
confidence: 94%
“…The fact that combining developmental support and assessment is possible under certain conditions was also concluded elsewhere [11,26,41]. Valentine and Schuwirth [41], for example, concluded that assessment by a coach needs to be perceived as 'fair' (credible, transparent, fit for purpose, and accountable), for a learner to accept it and learn from it. We noticed participants in the current study reasoned along similar lines: some told us it made sense that there was an assessment component to the mentoring role, as mentors were the one to see mentees grow, or not.…”
Section: Discussionmentioning
confidence: 94%